Docosahexaenoic acid in regio- and enantiopure triacylglycerols: Oxidative stability and influence of chiral antioxidant. (15th February 2023) - Damerau, Annelie; Ahonen, Eija; Kortesniemi, Maaria; Gudmundsson, Haraldur G.; Yang, Baoru; Haraldsson, Gudmundur G.; Linderborg, Kaisa M.
Highlights: First study on the oxidative stability of DHA in regio- and enantiopure TAGs. DHA in sn -2 was the most stable structure with or without RRR -α-tocopherol. Without tocopherol, oxidative stability of DHA in sn -1 and sn- 3 was comparable. With RRR -α-tocopherol, higher stability of DHA in sn -1 compared to sn -3. Diastereomeric interactions between RRR -α-tocopherol and DHA in sn -1 is proposed. Abstract: Docosahexaenoic acid (DHA) is essential for health but easily oxidized. Yet the influence of DHA's exact location ( sn -1, sn -2, or sn -3) in triacylglycerols on oxidative stability is currently unknown. This is the first study comparing oxidative stability of DHA in regio- and enantiopure triacylglycerols with or without RRR -α-tocopherol. Headspace solid-phase micro-extraction with gas chromatography–mass spectrometry, liquid chromatography–mass spectrometry, and nuclear magnetic resonance spectroscopy were applied. DHA in sn -2 was the most stable with or without added RRR -α-tocopherol resulting in differences in hydroperoxide formation. Without antioxidant, stability of DHA in sn -1 and sn -3 was mainly similar, with slight tendency towards better stability in sn -3. With RRR -α-tocopherol higher stability in sn -1 compared to sn -3 was observed. This points to diastereomeric interactions between RRR -α-tocopherol and DHA in sn -1. These results are highly relevant for enzymatic restructuring processes of DHA-rich fish or microalgae oil concentrates aimed for food supplements or food fortification.